Primaquine-induced hemoglobinuria: a case report of a G6PD deficient malaria patient with Mahidol trait from Bandarban, Bangladesh - Zamil, Md Fahad; Phru, Ching Swe; Hasan, Anamul; Trina, Afrida Tabassum; Shahbaz, Mohammad; Ahmed, Shahrear Tanvir; Hossain, Mohammad Sharif; Alam, Mohammad Shafiul (Frontiers in Malaria, 2025)
We report a case of Primaquine (PQ) induced hemoglobinuria in a patient with the glucose-6-phosphate dehydrogenase (G6PD) Mahidol variant from Bandarban, Bangladesh. The patient presented with mixed Plasmodium falciparum and Plasmodium vivax malaria and was recommended to be treated according to national guidelines with Artemether-Lumefantrine for three days and PQ for 14 days. Ten days later, the patient developed a fever and jaundice, followed by hemoglobinuria twelve days after the initial diagnosis. This highlighted the need for G6PD testing, which was subsequently confirmed by both Point-of-Care (POC) testing and spectrophotometry. The POC test showed a G6PD activity of 2.6 IU/g Hb, while spectrophotometry measured 1.47 IU/g Hb, both indicating G6PD deficiency (<30% activity). As a result, PQ was discontinued, and the patient received four units of blood transfusion. Additionally, genotyping was carried out, confirming the Mahidol variant. This case highlights the importance of routine G6PD screening before PQ administration, especially in malaria-endemic regions with different G6PD variants.